HUBUNGAN PIJAT BAYI DENGAN LAMA WAKTU TIDUR PADA BAYI - Angestu Erlawati; Ika Oktaviani; Yuliawati Yuliawati (Jurnal Kesehatan Metro Sai Wawai, 2017)
Sleeping has a great effect on mental health, emotional, physical and immune systems. Ineffective quality infant sleeping casuses the baby to experience sleep disturbance. Sekartini research results (2004) 44.2% of babies experience sleep disorders as often awakened at night. Pre-survey results in the Okta Midwife Private Practice in January 2017 showed 75% of babies awake at night and 42% of babies sleep 11 hours per day. One effort that can be done to help improve the quality and quantity of baby's sleep is a baby massage. The purpose of this study was to determine the relationship of infant massage with duration of sleep in infants aged 3-6 months. This type of research is pre experimental with one group pretest post test approach. The instrument of data collection using questionnaires. The sampling used nonprobability sampling technique with consecutive sampling method with 25 respondents. Univariate analysis used mean, median and bivariate analysis using dependent nonparametric statistical test Wilcoxon signed ranks test. The result of the research shows that the average length of baby's sleep before the treatment of baby massage is 12,88 hours. The average length of baby sleep after the baby massage treatment was 14.32 hours. The result of statistical test of infant massage relationship with duration of sleep in babies aged 3-6 months obtained p value 0,000. There is a relationship of infant massage with sleep duration in babies aged 3-6 months. Efforts in increasing the adequacy or enough of quality and quantity sleeping babies can be done by the way of early midwives teaching on how to massage the baby to a post partum woman in order to have a good quality and quantity sleeping.